CUSTOMER SWITCHING BEHAVIOUR OF AIRY ROOMS USERS USING PUSH-PULL-MOORING APPROACH - Ferania Ulva Amelia; Farah Oktafani (Jurnal Riset Bisnis dan Manajemen, 2021)
There are data that show a decrease in occupancy rates of star-rated hotels and rise of budget hotels in Indonesia. Supported by customer reviews which explain their reasons for choosing budget hotels over star hotels, this switching behavior may reduce the demand of star hotel services. This study aims to determine the Push-Pull-Mooring (PPM) factors on the intention and behavior of hotel service users. This study uses PPM with quantitative method using 400 samples. The samples were determined using Non-Probability Sampling, analyzed with SEM research analysis method and processed using SmartPLS. The results showed that PPM factors significantly affected the Switching Intention as well as Switching Behavior. However, Mooring factor does not have a significant effect on intensing switching either a significant influence on the Push and Pull factors of Switching Intention.